PENCIPTAAN KARYA TEKNIK SULAM MENGGUNAKAN BAHAN RAFIA PADA TAS TOTE BAG - Zola Savira; Purwosiwi Pandansari (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The creation of embroidery technique works using raffia material on tote bags is an effort to process Jepara motifs into textile works through embroidery techniques with raffia material. The production of embroidery technique works using raffia on tote bags involves the application of Jepara motifs with a flora theme on motif elements such as trubusan, jumbai, relug, and buah that have undergone stylization and simplification processes. The processing of raffia modified as thread, namely split and twisted for embroidery work, is able to create a more prominent visual. The strong, pure, and functional characteristics make the tote bag made of blacu material chosen as the embroidery medium. The purpose of this creation is to understand the process and results of creating embroidery works using raffia on tote bags. This research uses a practice-based art approach (Practice-Based Research / PBR) with the theory of craft art creation that has three main stages within it, namely exploration, planning, and realization. The creation results in three tote bags with raffia embroidery techniques featuring Jepara motifs with a flora theme that have unique texture and visual beauty.